Vertebroplasty with posterior spinal fusion for osteoporotic vertebral fracture using computer-assisted rod contouring system: A new minimally invasive technique. (2020) - Funao, Haruki; Isogai, Norihiro; Sasao, Yutaka; Nishiyama, Makoto; Ishii, Ken
Highlights: Surgical treatment of osteoporotic vertebral fracture (OVF) is challenging. A new minimally invasive technique of posterior spinal fusion was performed for OVF. This technique would be beneficial for elderly or immunocompromised patients. Abstract: Introduction: Surgical treatment of osteoporotic vertebral fracture (OVF) has been challenging for spine surgeons, because there are potential risks of instrumentation failure; such as screw loosening, loss of correction, or pseudarthrosis, due to bone fragility in elderly patients with several comorbidities. Presentation of case: A 68-year-old female presented with a severe low back pain and bilateral thigh pain. She had a history of systemic scleroderma, which was complicated by interstitial lung disease. Although she initially underwent non-surgical treatment with bracing for 7 months, her symptoms had progressively deteriorated, and her radiographs showed non-union at L1 and progressive kyphotic deformity at the thoracolumbar spine. Because an anterior approach was inadvisable due to interstitial lung disease, vertebroplasty with posterior spinal fusion was performed using percutaneous pedicle screws (PPS) at the upper most and lowest instrumented vertebra combined with sublaminar taping and computer-assisted rod contouring system. Good bony union was achieved with no screw loosening at 1-year follow-up. Discussion: Various surgical procedures have been applied according to the fracture type or medical condition of the patient. Minimally invasive posterior spinal fusion would be a less invasive approach in patients with poor medical condition. PPS can prevent the excessive dissection of paravertebral muscles, and this is especially advantageous at the proximal and distal end of long constructs. A recent computer-assisted rod contouring system accurately matches each screw head resulting in reduced strength of the screw-bone interface. Conclusion: This technique would be beneficial in the elderly or immunocompromised patients with OVF.